Heavy metals in the system «bottom sediments − water vegetation» river ecosystems in the supervised area of the Belarusian nuclear power plant - Pоzdniakova, Anastasiya I. (Journal of the Belarusian State University. Ecology, 2020)
The article describes and presents the main results of heavy metals measurements in bottom sediments sampled in surface waters in the water objects of the Belarusian NPP, obtained in 2017. There are presented the measuring concentrations of 10 heavy metals included in the controlled pollutants by the National Environmental Monitoring System (NEMS) of the Republic of Belarus and the Food and Agriculture Organization of the United Nations (FAO) of the World Health Organization (WHO). The measurements were carried out on the basis of the RUE «Scientific and Practical Center of Hygiene». There is presented the analysis of the results and comparison with regional clarks and current standards (maximum permissible concentrations). The containing of heavy metals mobile forms was measured, and the mobility coefficient of heavy metals in bottom sediments was calculated. There are evaluated biological absorption coefficient of heavy metals in samples of aquatic vegetation and mixed grass and biogeochemical activity of aquatic vegetation certain species (Elodea canadensis, Batrachion trichophyllum, Glyceria fluitans).
Keywords: bottom sediments; background monitoring; heavy metals; maximum allowable concentration; clark; mobility coefficient; biological absorption coefficient; biogeochemical activity coefficient; Belarusian NPP